Human Amniotic Epithelial Cells and Their Derived Exosomes Protect Against Cisplatin-Induced Acute Kidney Injury Without Compromising Its Antitumor Activity in Mice - Kang, Xin; Chen, Ying; Xin, Xiaohong; Liu, Menghan; Ma, Yuan; Ren, Yifei; Ji, Jing; Yu, Qi; Qu, Lei; Wang, Suxia; Liu, Gang; Xiang, Chengang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Cisplatin is a widely used chemotherapeutic drug, whereas the clinical application is greatly limited by its nephrotoxic side effect. Currently, there has been no effective treatment to prevent cisplatin-induced acute kidney injury (cisplatin-AKI). Human amniotic epithelial cells (hAECs) and their derived exosomes (EXOs) have been proven to effectively protect against ischemia reperfusion-induced AKI, yet their roles in cisplatin-AKI are still unknown. Methods: C57BL/6J mice were given two doses of cisplatin at 20 or 15 mg/kg of body weight to induce AKI with or without mortality. hAECs or EXOs were injected via tail vein 1 day after cisplatin administration. Serum and kidney tissues were collected on the fourth day after 15 mg/kg cisplatin treatment to explore the nephro-protective effects of hAECs and EXOs on cisplatin-AKI. Lung cancer xenograft model was built by subcutaneous injection of A549 cells into BALB/c nude mice to evaluate the effect of hAECs or EXOs on cisplatin chemotherapy. Results: Cisplatin nephrotoxicity was significantly attenuated by hAECs and EXOs as evidenced by reduced mortality rate and decreased serum creatinine (sCr) and reduced tubular injury score. hAECs or EXOs exerted the nephro-protective effects via suppression of TNF-α/MAPK and caspase signaling pathways. In the A549 lung cancer xenograft mouse model, administration of hAECs or EXOs did not promote tumor growth or compromise the therapeutic effects of cisplatin on tumors. Conclusion: This study is the first to demonstrate that hAECs and their derived exosomes have nephro-protective effects in cisplatin-AKI in vivo. Importantly, neither hAECs nor EXOs compromise the antitumor activity of cisplatin. These results potentially support the use of hAECs and their derived EXOs as nephro-protectors against cisplatin-induced nephrotoxicity clinically.